The Influence of Experiential Learning, Social Learning, Formal Learning on Improving the Performance of PT Bank Negara Indonesia (Persero), Tbk Employees in the Central Sulawesi Area Region 11 Manado With Digital Mindset as an Intervening Variable - Kamasaan, Raymond Bastian; Kambuaya, Balthasar; Tuhumena, Ruben; Erari, Anita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to examine and analyze the influence of experiential learning on digital mindset, the influence of social learning on digital mindset, the influence of formal learning on digital mindset, the influence of experiential learning directly and indirectly through digital mindset on employee performance, the influence of social learning directly and indirectly through digital mindset on performance employees, the influence of formal learning directly and indirectly through digital mindset on employee performance, the influence of digital mindset on employee performance. This research is a descriptive type with a quantitative analysis method. The sample in this study was 163 employees from the Parigi, Palu, Luwuk and Tolitoli branch offices. The research instrument was tested using validity tests and reliability tests, while the data analysis technique used descriptive analysis, regression analysis and path analysis which were arranged in structural equation modeling (SEM) using the smart PLS application. The research results showthat; 1) experiential learning has a significant effect on digital mindset; 2) Social learning has a significant effect on digital mindset. 3) formal learning has a significant effect on digital mindset; 4) experiential learning directly has a significant effect on performance and experiential learning indirectly through digital mindset has a significant effect on performance; 5) social learning has a significant effect on performance and social learning indirectly through digital mindset has a significant effect on performance, 6) formal learning has no significant effect on performance and formal learning indirectly through digital mindset has a significant effect on performance; 7) digital mindset has a significant effect on performance.